Pancasila State: Study of Concepts, State Philosophy, Paradigms, Existence, Guidelines, and Relevance with Maqasid Al-Shari'ah Jamal Al-Din 'Atiyyah - Muhammad Solikhudin; Moh. Faizur Rohman (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2023)
This article aims to strengthen the ideology of Pancasila and to answer the fundamental problems of the state which are being debated between the secular state, the religious state, and the state of mutualist symbiosis with the ideology of Pancasila, which in this article is discussed with the Pancasila state. This article explains the Pancasila state by examining concepts, state philosophy, paradigm, existence, guidelines, and relevance to maqasid al-shari'ah Jamal al-Din 'Atiyyah. The type of research used is library research with qualitative analysis techniques and a conceptual approach. The research results state that the Pancasila state concept is a prismatic concept built between a religious and secular state, individualism and collectivism, and civil law and common law. Pancasila is a state philosophy that contains common interests and originates from political agreement. The Pancasila State is a legal paradigm and its development. In the realm of existence, Pancasila emphasizes the relationship between religion and the state. For this reason, there are four guiding principles of national law; firstly, all laws must guarantee the nation's integration. Secondly, laws must be created democratically and nomocratically based on the wisdom of wisdom; thirdly, laws must encourage the creation of social justice; and fourthly, there must not be public laws based on certain religious teachings. The Pancasila state was created to create a harmonious life in diversity because Pancasila is a way of life that promotes mutual harmony. Meanwhile, the relevance of Jamal al-Din 'Atiyyah's maqasid al-shari'ah is related because it contains maqasid personalmukallaf, maqasid al-ummah (national goals), and maqasid al-insanity (humanitarian goals). Keywords: State, Pancasila, and maqasid al-shari'ah Jamal al-Din 'Atiyyah.